What is Participatory Rangeland Management? - International Livestock Research Institute (International Livestock Research Institute, 2023)
Participatory rangeland management (PRM) is a community-led process for improving the management and governance of rangelands, supported by facilitators and technical advisors. This animated film describes the process, and in particular the use of the 'four legs' goat, to understand the four main pillars of PRM.